Biological Evaluation of Chiral Amides Synthesized from Diacetyl-L-tartaric Acid and Aromatic Amines - Malik, Mahrukh; Wali Khan, Sher; Arfan, Muhammad; Hussain Zaidi, Javid; Bano, Asghari; Ullah, Faizan (Asian Journal of Chemistry, 2012)
L-Tartaric acid is chiral compound and commercially available was conveniently converted into diacetyl-L-tartaric acid anhydride. Diacetyl-L-tartaric acid anhydride was then made to form half ester of diacetyl-L-tartaric acid anhydride which was then reacted with substituted anilines to yield respected chiral amides. These chiral amides were further purified and were characterized by using 1H NMR. The compound E11 [methyl-2,3-diacetoxy-4-oxo-4-(2’- methoxyphenylamino)butanoate] showed greater antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae. However, maximum antifungal activity was recorded for E3 [methyl-2, 3-diacetoxy-4-oxo-4-(4’-bromophenyl amino)butanoate]. The compounds E2 [methyl-2,3-diacetoxy-4-oxo-4-(2’-bromophenyl amino)butanoate] and E3 completely inhibited the germination of canola seeds, whereas, the compounds E1 [methyl-2,3- diacetoxy-4-oxo-4-(4’-methyl phenyl amino)butanoate] and E11 [methyl-2,3-diacetoxy-4-oxo- 4-(2’-methoxyphenylamino)butanoate] caused 40 % inhibition of seed germination.